The objective of considering SMEs in the context of comparative institutional analysis in the Japanese economy : Closing the gap to the international economy / Hiromasa Nakamura - Nakamura, Hiromasa (Universiti Teknologi MARA Cawangan Pahang, 2007)
It would be difficult to overstate the importance of the recovery of the Japanese Economy, and Small and Medium Enterprises in Japan have constantly strived to overcome the structural recession. Japan's international competitive advantage is primarily value-added manufacturing and trade, and the recovery of the Japanese Economy is in relation to the exportation of electronics to China and automobiles to the United States. On the other hand, most Japanese SMEs are facing confusion in the structural reform in the fields of manufacturing, commerce and SME Finance.